Molluscs production associated to lunar-tide cycle: a case study in Paraíba State under ethnoecology viewpoint - Alves Rômulo RN; Nordi Nivaldo; Nishida Alberto K (BMC, 2006)
Abstract Molluscs have been for a long time a very important food resource for humans. Therefore, oysters, clams, and mussels are highly required at seafood markets. Like any commercial food, it is necessary that molluscs present good quality standards, concerning some criteria such as amount of meat and appearance. In bivalves, condition index or fattening index is considered a satisfactory method for estimating the amount of meat related to the shell cavity. Molluscs gatherers of Paraíba State coast, northeastern Brazil, state that molluscan meat production increases during spring tide (designated by them as maré de lançamento) in opposition to the meat decrease which happens during neap tide (maré de quebramento) (they are designated technically in Portuguese as maré de sizígia and maré de quadratura, respectively). Weperformed a survey on the production of unha-de-velho or 'oldman'snail' (Tagelus plebeius) caught by molluscs gatherers in the estuary of River Paraíba do Norte, by observing locally their work, applying questionnaires, searching for a possible scientific relation of that molluscs condition to the gatherers empirical statement. Thus, we estimatedthe molluscs condition index through the method of solids percentage determination. We studied their work and the molluscs condition index during a full lunar-tide cycle. Determinations were carried out between 2nd September and 20th October, 1998, through 20 catches performed to obtain condition index from 400 bivalves. We observed that several biotic and abiotic ecological factors, namely reproduction cycle, biochemical components variations, animal size, and even parasitism, may affect the animal condition index. Despite this aspect, our present results confirmed a high overlapping (80%) of the condition index curve with lunar-tide cycle, in agreement with the gatherers statement. Although we recognize the need for formulating and testing other hypotheses, we consider a priori that the gatherers empirical assertion a unha tá gorda de acordocom a maré ('the "oldman's nail" is fat according to the tide', roughly translating) is justified by the observations here performed when the condition index increased during spring tide and decreased during neap tide.